2010
DOI: 10.1177/1756283x10379258
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effects of Coltect, a novel dietary supplement, alone and in combination with 5-aminosalicylic acid in 1,2-dimethylhydrazine-induced colon cancer in rats

Abstract: Abstract:Objectives: Coltect is a novel dietary supplement containing curcumin, green tea and selenomethionine. Previous reports have suggested that these agents can prevent colorectal cancer (CRC). The present study examined the chemopreventive effect of Coltect alone or combined with 5-aminosalicylic acid (5-ASA) using the 1,2-dimethylhydrazine (DMH) model in rats. Methods: The effect of Coltect was examined on HT-29 CRC cells by growth inhibition assay. Apoptosis was determined by annexin V-FITC/PI staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Coltect reduced the number of aberrant crypt foci similarly as 5-aminosalicylic acid by 40 %. The use of both substances resulted in a synergistic effect, reducing the number of aberrant crypt foci by 70 % [ 52 ].…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Coltect reduced the number of aberrant crypt foci similarly as 5-aminosalicylic acid by 40 %. The use of both substances resulted in a synergistic effect, reducing the number of aberrant crypt foci by 70 % [ 52 ].…”
Section: Dietary Factorsmentioning
confidence: 99%
“…We chose 10 % (w/v) DMH (1, 2-dimethylhydrazine) saline solutions at doses of 40 mg/kg body weight per animal as our experimental carcinogenesis reagent. DMH is a commonly used chemical carcinogen with selectivity for the colorectum, and it induces a carcinogenic process similar to that of spontaneous human colorectal cancer [ 19 21 ]. The CRC group rats were induced with DMH for 20 weeks, and the histopathology of each rat rectum was examined on 4th, 8th, 12th, 16th and 20th weeks after DMH induction (Figure 1 ) From the histopathology of the carcinogenic process induced by DMH, it was concluded that CRC developed from mucosal hyperplasia to invasive carcinoma during our experiment.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 78 rats were divided into two groups, CRC rats ( n = 48) and normal rats ( n = 30). The CRC rats were given DMH solutions as described previously [ 19 20 ]. Briefly, the CRC rats received intraperitoneal injections of DMH solution (DMH dissolved in saline to produce 10 % solutions) at a dosage of 40 mg/kg once a week for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The study was approved by the Institutional Committee for Animal Welfare of the Tel-Aviv Sourasky Medical Center (protocol number 1-12-09). 14 …”
Section: Methodsmentioning
confidence: 99%
“…13 We have shown that the most effective ratios of the three ingredients for cancer prevention in a rat model are curcumin (500 mg), green tea (250 mg) and selenomethionine (100 µg) (Coltect, Israel). 14 Herein, the efficacy of the combination is shown in the DSS model in mice, and validated in a 2,4,6-trinitrobenzenesulfonic acid (TNBS) model in rats. In the clinical setting our results suggest that Coltect may be an effective treatment in patients experiencing mild-to-moderate UC; however, in order to confirm its clinical efficacy larger trials are required.…”
Section: Introductionmentioning
confidence: 99%